Nonlinear multiple-input-multiple-output adaptive backstepping control of underwater glider systems. (8th December 2016) - Cao, Junjun; Cao, Junliang; Zeng, Zheng; Lian, Lian
In this article, an adaptive backstepping control is proposed for multi-input and multi-output nonlinear underwater glider systems. The developed method is established on the basis of the state-space equations, which are simplified from the full glider dynamics through reasonable assumptions. The roll angle, pitch angle, and velocity of the vehicle are considered as control objects, a Lyapunov function consisting of the tracking error of the state vectors is established. According to Lyapunov stability theory, the adaptive control laws are derived to ensure the tracking errors asymptotically converge to zero. The proposed nonlinear MIMO adaptive backstepping control (ABC) scheme is tested to control an underwater glider in saw-tooth motion, spiral motion, and multimode motion. The linear quadratic regular (LQR) control scheme is described and evaluated with the ABC for the motion control problems. The results demonstrate that both control strategies provide similar levels of robustness while using the proposed ABC scheme leads to the more smooth control efforts with less oscillatory behavior.